Using risk sharing contracts for supply chain risk mitigation: A buyer-supplier power and dependence perspective. (January 2017) - Ghadge, Abhijeet; Dani, Samir; Ojha, Ritesh; Caldwell, Nigel
Highlights: Development of a novel supply chain risk sharing contract to mitigate demand uncertainty and price volatility. Multiple buyer-supplier power and dependence scenarios to reflect leverages involved in the decision-making. Research contributes by providing a relational perspective into dynamics of supply chain design and collaboration. Abstract: The paper aims to understand buyer-supplier power and dependence scenarios following a risk sharing contract. The study develops a supply chain risk sharing contract to mitigate demand uncertainty and price volatility related risks in a globalised business environment. An integer programming model is developed and analysed following an automotive case study to generate insights into buyer-supplier relationships. Multiple buyer-supplier power and dependence scenarios are considered to reflect the possible leverages involved in the decision-making. The situational strength evaluated through buyer-supplier power and dependence illuminates the inherent complexity in contract negotiation. Thus there is an evident need to develop risk sharing contracts for mitigating global risks. The developed relationship framework and risk sharing contract model are expected to help SC managers in better understanding behavioural aspects during contract negotiations. The risk sharing contract model proposed here also contributes to a potentially novel perspective on existing theory in buyer-supplier power and dependence by providing a relational perspective on the dynamics of supply chain design and collaboration.